Medial meniscus lesions in tennis player: 9 case reports - Daubinet, G. (2001)
This study investigated the outcomes of meniscectomies performed for medial meniscus lesions in elite tennis players (1st and 2nd series) under 30 years of age. The menisci perform several important functions in the knee: shock absorption, division of the pressure and of the fluid of the joint, and joint stabilisation. Only the peripheral third and a large part of the anterior and posterior horn contain blood vessels and nerves. The lateral menisci are larger, rounder, and more mobile. They are separated from the articular capsule by the popliteal tendon at the posterior-external aspect. The force transmitted by the knee is approximately 2 to 4 times the body weight. The menisci transmit between 50% and 100% of this weight. Lesions therefore occur as a result of compression or tearing during rotation, semi-flexion or gliding.